Pengembangan Perangkat Pembelajaran Geometri dengan Pendekatan Realistic Mathematics Education (RME) Berbantuan Cabri 3D - Nurul Asma; M. Ikhsan; Hajidin Hajidin (Universitas Syiah Kuala, 2019)
Interest geometry are taught is to develop spatial ability so as to impart knowledge to support other materials. As NCTM specify one of five content standards in mathematics, namely geometry measurement an important element involves the use of visualization and modeling. This shows that modeling is the demands of the curriculum that must be accommodated in the classroom. Therefore, teachers should be able to apply the learning object model that abstracts from geometry into real situations imaginable learners. One lesson that applies the use of models that help learners build their own knowledge is Realistic Mathematics Education (RME). Shaped media selection Information and Computer Technology (ICT) can also meet the demands of the curriculum on the use of visualization to teach geometry. One of ICTs to facilitate learners to imagine something abstract geometry of the object is Cabri 3D software. But in reality there is no learning device that integrates Cabri 3D geometry once using RME approach. This study aims to develop and produce devices RME-assisted learning Cabri 3D is valid, practical, and effective. This research is a research development refers to the model of Dick and Carey consisting of nine steps, namely the identification of learning objectives, learning analysis, identification of the characteristics of learners, formulate learning objectives, develop test items, develop learning strategies, develop learning materials, design and implement formative evaluation, and revising instructional materials. The trial in this study conducted in SMP 19 Pilot Banda Aceh. The result showed that the learning device geometry with Cabri 3D-assisted RME approach memenui valid criteria, practical andeffective.